On Chinese Hegemony in Africa’s Development Agenda: A Critical Perspective on the Belt and Road - Diemas Sukma Hawkins (TRANSBORDERS: International Relations Journal, 2026)
Using Cox’s Critical Theory of Hegemony and the Three Categories of Forces, this paper analyzes China’s strategy in developing a Sino-centric development agenda in Africa. First, it explores the history of China’s relationship with Africa and the shift from China’s relative isolationist approach to foreign policy to a more active role in global governance. Second, it explores the institutions developed in the twenty-first century that can support China’s global agenda such as BRICS, the African Union, and the Belt and Road, as well as the financial architecture China attempts to establish for an alternative global financial system. Finally, the paper explores China’s use of its material capabilities such as its financial wealth, industrial capabilities, and technological advancement to reshape Africa in a way that benefits its interests.